Experience, brand prestige, perceived value (functional, hedonic, social, and financial), and loyalty among GROCERANT customers - Kim, Seoyoung; Ham, Sunny; Moon, Hyeyoung; Chua, Bee Lia; Han, Heesup (Elsevier, 2019)
The food service industry has already observed that a merely good quality of products/services cannot make a business successful and has emphasized the importance of delivering unique and memorable experiences. Grocerants meet customer demand by filling the roles of grocery stores and restaurants, while offering novel and special experiences to customers. This study explores the unique experiences staged in grocerants by applying the experience economy and associates such experiences to brand prestige, customer perceived value, and loyalty. Data was collected at grocerants in Korea, using a mall-intercept survey. Our results identify the positive effects of entertainment and escapist experiences on brand prestige which significantly triggers functional, hedonic, social, and financial values. The three values (functional, hedonic, and financial) also affect loyalty. Overall, the proposed theoretical framework sufficiently accounts for customer loyalty. This study was the first attempt to investigate grocerant patrons’ behaviors and thus includes a high degree of originality.